Modern Professional Language of Robotics (Terminological Family “Robot”) - A. S. Zaitseva (Научный диалог)
The article is devoted to the study of the terminological family with the base term “robot”. The issues concerning the structure of the terminological family, its basic lexical units, the most productive models of term formation and most frequent grammatical forms of terms are considered. Particular emphasis is placed on the specifics of the terminological family. The characteristic features of terminological elements used in the formation of new terms are defined. It is emphasised that the emergence of terminological combinations is a common way of forming new special words. In the course of study, it was found that the terminological family with the base term “robot” belongs to the class of highly deployed families. A five-stage model of the terminological family is presented. About 200 derived terms have been analysed at the five stages of term formation relating to the present state of language development. The scientific hypothesis that the emergence of terms-specifiers of the original concept is the way of forming a special professional terminological family has been proved. The material for research includes the “English-Russian Explanatory Dictionary” by E. M. Proydakov and L. A. Teplitskiy (Moscow, 2019), monographs, scientific publications on robotics in peer-reviewed journals in 2010—2021.